Cervical Myelopathy Caused by Posttraumatic Osteophytes Resulting From Long-Standing Neglected Posterior Atlanto-Occipital Dislocation More Than 30 years: A Case Report. (4th October 2021) - Chang, Dong-Gune; Park, Jong-Beom; Park, Soo-Bin; Kim, Hong Jin
Abstract : Introduction: Traumatic atlanto-occipital dislocation (AOD) is a rare but usually fatal injury. To our knowledge, no study has reported long-standing neglected posterior AOD more than 30 years in a patient who survived and later experienced cervical myelopathy. Methods: A 75-year-old man presented with symptoms of cervical myelopathy. On history, the patient was diagnosed with posterior AOD that occurred after a fall 31 years ago, but he did not undergo surgery. Radiologic evaluation of cervical spine revealed severe spinal cord compression caused by posttraumatic osteophytes of the C0-C1-C2 joints resulting from long-standing neglected posterior AOD. However, no instability of the C0-C1-C2 joints was found. Results: Laminectomy of the C1 posterior arch was performed without occipitocervical fusion considering the long-standing severe osteoarthritic changes and no instability of the C0-C1-C2 joints. Cervical myelopathy significantly improved, and the patient was doing well without recurrence at the 7-year follow-up. Discussion: To our knowledge, this is the first report of a patient with cervical myelopathy caused by neglected posterior AOD with posttraumatic osteophytes of the C0-C1-C2 joints. Laminectomy of the C1 posterior arch without occipitocervical fusion achieved satisfactory outcomes for cervical myelopathy caused by posttraumatic osteophytes resulting from long-standing neglected posterior AOD more than 30 years.